America's War in Vietnam : A Short Narrative History - Addington, Larry H. (Book collections on Project MUSE., 2000)
"If you want to read one book about Vietnam, read this one."--New York Review of Books Drawing on years of experience teaching about the war, Larry H. Addington presents a short, narrative history of the origins, course, and outcome of America's military involvement in Vietnam. Not intended as a competitor to the many excellent comprehensive studies of the Vietnam Era, this book will prove a useful introduction and a concise reference to America's longest, most controversial war. Addington reviews the history of pre-colonial Vietnam, the impact of French imperialism and the Indochina War, and the Cold War origins of American involvement. He then details US policy after the 1954 Geneva Accords, its role in the establishment of South Vietnam, and the outbreak of a new war. Turning to America's deepening involvement, Addington examines the US strategies for waging air and ground war, the impact of the war at home, and the reasons for the failure of US policy under President Johnson. He studies the successes and failures of the policy of withdrawal under President Nixon and concludes with an overview of the war's aftermath and its legacy